Phase 1 dose-escalation study of oral abexinostat for the treatment of patients with relapsed/refractory higher-risk myelodysplastic syndromes, acute myeloid leukemia, or acute lymphoblastic leukemia. Issue 8 (3rd August 2017) - Vey, Norbert; Prebet, Thomas; Thalamas, Claire; Charbonnier, Aude; Rey, Jerome; Kloos, Ioana; Liu, Emily; Luan, Ying; Vezan, Remus; Graef, Thorsten; Recher, Christian
Abstract: Histone deacetylase (HDAC) inhibitor abexinostat is under investigation for the treatment of various cancers. Epigenetic changes including aberrant HDAC activity are associated with cancers, including myelodysplastic syndromes (MDS), acute myeloid leukemia (AML), and acute lymphoblastic leukemia (ALL). In this phase 1 dose-escalation study, 17 patients with relapsed/refractory higher-risk MDS, AML, or ALL received oral abexinostat (60, 80 [starting dose], 100, or 120 mg) twice daily (bid) on Days 1–14 of 21-day cycles. The most common treatment-related grade ≥3 adverse events were thrombocytopenia (29%) and neutropenia (24%), none of which led to discontinuation. Maximum-tolerated dose was not reached. Of 12 evaluable patients, best response was stable disease in 1 patient. This study was closed due to limited clinical benefit. Future development of oral abexinostat 100 mg bid in patients with MDS, AML, or ALL should focus on combination regimens. ISRCTN registry: 99680465